2020
DOI: 10.29408/veles.v4i2.2543
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception on Online Application in Speaking Skill

Abstract: Online applications become a medium that helps the learning process of English in the classroom easier. Many online applications can be used to learn to speak English. Therefore, the aim of this study is to identify suitable online applications for learning to speak English that suits student needs. The research method uses descriptive qualitative. The data collection process is interview, observation, and questionnaire. Data analysis used three steps, namely data reduction, data display, and conclusion drawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…It is shown in Figure 1 that the experimental group which consisted of 5 students and a native speaker, performed well-organized virtual interview through Zoom Cloud Meeting and they enjoyed the learning process. These findings complement to the previous work of Baron (2020) that using an online media such as Zoom Cloud Meetings to perform dialogue tasks is preferred by students while also improve their speaking skills. Figure 1.…”
Section: Volume 19 No 01 Maret 2021supporting
confidence: 85%
See 1 more Smart Citation
“…It is shown in Figure 1 that the experimental group which consisted of 5 students and a native speaker, performed well-organized virtual interview through Zoom Cloud Meeting and they enjoyed the learning process. These findings complement to the previous work of Baron (2020) that using an online media such as Zoom Cloud Meetings to perform dialogue tasks is preferred by students while also improve their speaking skills. Figure 1.…”
Section: Volume 19 No 01 Maret 2021supporting
confidence: 85%
“…Other studies about interview but in online media were conducted by some researchers such as Authar & Afandi (2020) and Baron (2020) They observed their students speaking skills with pairs and group interviews through video conference. Baron (2020) stated that his students preferred using Zoom Cloud and Google Hangout Meetings to improve their speaking skills through dialogue with their classmate, while Youtube was chosen to do monologue by recording and uploading it thus the lecturer could examine their speaking capability well. In the other hand, Authar & Afandi (2020) added that using Task Based Language Instruction to assign the students for interviewing in pairs through online video conference had some benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The features of video conferencing, recording, sending message, and storage materials uploaded by the teacher make GM and GC preferable for online education. Baron (2020) confirms in the research that GM is found practical and easy to use in speaking lessons by students. In line with these findings, the present study signifies the effectiveness of these platforms to use with Oral Communication Skills course as students highlighted the features which help them share their opinions and comment on their friends' thoughts.…”
Section: Benefits Of Using Google Meet and Google Classroomsupporting
confidence: 74%
“…In the line similar conducted (Baron, 2020) discovered that studying English online have numerous elements such as pace, are direct and indirect strategies, as determined by a SILL (strategy inventory for language learning).…”
Section: Introductionmentioning
confidence: 99%